“From the Outhouse to the Center of the House”. About the New Spatial and Cultural Dimension of the Kitchen in Contemporary Interior Design - Kowalczyk, Paulina (In the Kitchen. Cultural Sketches on Space, 2019)
In the article author shows how the significance of the kitchen has changed and what cultural and symbolic factors influenced that in modern home’s “geography” this space was marginalized. Author poses questions about the sustainability of some figures of imagination, which determined the spatial hierarchy in the home. Analyzing old-time architectural guides and treatises as well as contemporary magazines and websites devoted to interior design, author tries to show these changes and a new spatial and cultural dimension of kitchen.